Forgotten contributions to scientific management: work and ideas of Karol Adamiecki. Issue 1 (12th January 2015) - Debicki, Bart J.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to present the work and contributions of Karol Adamiecki in comparison with Frederick Winslow Taylor and discusses the various contexts in which both scholars conducted their research. The purpose of this study is bring to light some of the main accomplishments of Adamiecki and contribute to the discussion of reasons why the work of some scholars draws wide acclaim, while similar work of others remains unnoticed. Design/methodology/approach – The background for the discussion is the work and ideas of Karol Adamiecki, a Polish engineer and manager, whose methods and findings were similar to those of Frederick Taylor and are contemporary, and, in some cases, precede those of the Father of Scientific Management. The methodology used in this study is a review of the original work of Adamiecki and Taylor to find the true meaning and purpose behind their writings, as well as a review of relevant literature regarding the context of the realities in which both scholars constructed their research. Findings – The concepts and inventions of Karol Adamiecki are, in many aspects, similar to those of Frederick Taylor and his followers. Several factors are identified and discussed which may have influenced the varied level of recognition of conceptually similar ideas evolved in different parts of the world. These factors are, among others, the socio-political reality of Eastern Europe and Poland under the influence of Russia and the Soviets as compared to that of the USA and the Western World and the support of various interest groups and government institutions, as well as the impact of the academic circles. Research limitations/implications – In today's world of globalization reaching all aspects of life, it is necessary to recognize and acknowledge the developments emerging in different settings, regions and cultures. Furthermore, the social and political realities in which research is constructed may impact the future acceptance, dissemination and popularity of the findings and authors. Originality/value – Although some research exists outlining the work of Adamiecki, this study contributes to the body of historical management knowledge by focusing on the main accomplishments of Adamiecki based on his original writings and placing his accomplishments in a historical context in comparison to Taylor, thus analyzing the reasons for the lack of wider acclaim for Adamiecki's contribution to scientific management.